Pakistan Development Update, June 2019 : Weathering the Storm - Restoring Macroeconomic Stability - World Bank (World Bank, Washington, DC, 2019)
Pakistan is facing yet another balance of payment crisis. Authorities have taken some corrective measures and negotiated a 39-month stabilization program with the International Monetary Fund (IMF). Nonetheless, inflationary pressures increased during FY19. Current account deficit narrowed as imports declined, however, exports performance remained weak. Despite the adjustment measures fiscal pressure persist due to high debt servicing and defense expenditures. Debt level is in breach of Fiscal Responsibility and Debt Limitation Act (FRDLA). The growth is projected to decelerate further in FY20, as the government tightens fiscal and monetary policy. This report highlights the importance of tackling the structural challenges which are hampering growth and investments. The report emphasizes that the failure to address these structural challenges, in parallel to addressing the macroeconomic imbalances, just means that the next crisis is another 4 to 5 years away.